Manufacturing method of lithium tantalate substrate

By embedding single crystal wafers in a mixed powder and controlling container spacing in the heating furnace, the method addresses conductivity and color uniformity issues in lithium tantalate substrates, enhancing their suitability for surface acoustic wave devices.

JP7615825B2Active Publication Date: 2025-01-17SUMITOMO METAL MINING CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021053405
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-26
Publication Date
2025-01-17
Estimated Expiration
2041-03-26

AI Technical Summary

Technical Problem

Existing methods for manufacturing lithium tantalate substrates face issues with insufficient conductivity improvement due to pyroelectricity, leading to charge buildup and electrode damage, and high Al powder ratios cause localized reduction unevenness, resulting in color shading and decreased productivity.

Method used

The method involves embedding single crystal wafers in a mixed powder of aluminum and aluminum oxide, sealing the container, and arranging the containers in a heating furnace with a space occupancy rate of 50% or less to maintain even gaps, ensuring uniform heat treatment and reducing local temperature unevenness.

Benefits of technology

This approach suppresses color unevenness and enhances conductivity, enabling the production of lithium tantalate substrates with improved electrical properties suitable for surface acoustic wave devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007615825000002
    Figure 0007615825000002
  • Figure 0007615825000003
    Figure 0007615825000003
  • Figure 0007615825000001
    Figure 0007615825000001
Patent Text Reader

Abstract

To provide a method for manufacturing a lithium tantalate substrate (hereinafter LT) which is suppressed from having color irregularity (shade difference) due to reduction unevenness.SOLUTION: A method for manufacturing a lithium tantalate substrate has the processes of: embedding a plurality of LT single crystal wafers (hereinafter wafers) in mixed powder of aluminum powder and aluminum oxide powder charged in a container, and sealing a container open part to constitute a single crystal wafer housing body (hereinwafer a wafer housing body) 10 in which the wafers are housed; and arranging a plurality of wafer housing bodies in a sealed room of a heating furnace which has the sealed room 30, and then heat-treating the wafers in a sealed atmosphere at a Curie temperature below the LT single crystal after filling the sealed room with an inert gas, in which the space occupation rate of all the wafer housing bodies in the sealed room is 50% or less, sufficient gaps can be secured among wafer housing bodies since the space occupation rate is 50% or less, and local temperature unevenness of each wafer housing body is avoided to suppress color unevenness (shade difference).SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for manufacturing a lithium tantalate substrate by subjecting a single crystal wafer obtained by slicing a lithium tantalate single crystal to a reduction treatment, and in particular to a method for manufacturing a lithium tantalate substrate in which the occurrence of color unevenness (difference in shading) caused by uneven reduction is suppressed. [Background technology]

[0002] Lithium tantalate (sometimes abbreviated as LT) single crystal is a ferroelectric material with a melting point of about 1650°C and a Curie temperature of about 600°C, and lithium tantalate substrates (LT substrates) manufactured using this single crystal are mainly used as surface acoustic wave (SAW) filter materials for use in transmitting and receiving devices in mobile phones. With the increasing frequency of mobile phones and the spread of Bluetooth (registered trademark) (2.45 GHz), a wireless LAN for various electronic devices, it is predicted that there will be a rapid increase in SAW filters in the frequency range of around 2 GHz in the future.

[0003] The SAW filter has a structure in which a pair of comb electrodes made of a thin metal film such as Al or Cu is formed on a substrate made of a piezoelectric material such as LT, and this comb electrode plays an important role in determining the characteristics of the device. The comb electrodes are formed by forming a thin metal film on the piezoelectric material by sputtering, and then removing unnecessary parts by etching using photolithography technology, leaving a pair of comb patterns.

[0004] Moreover, the above-mentioned LT single crystals are industrially grown mainly by the Czochralski method in an electric furnace in a nitrogen-oxygen mixed gas atmosphere with an oxygen concentration of several percent to about 20%, and usually, a high-melting point iridium crucible is used. The grown LT single crystal is cooled at a predetermined cooling rate in the electric furnace and then removed from the electric furnace.

[0005] The grown LT single crystal is colorless and transparent or has a highly transparent pale yellow color. After growth, it is heat-treated under soaking at a temperature close to the melting point to remove residual strain due to thermal stress in the crystal, and then a poling process is performed to make it single-polarized. In other words, the LT single crystal is heated from room temperature to a specified temperature above the Curie temperature, a voltage is applied to the crystal, and the temperature is lowered to a specified temperature below the Curie temperature while the voltage is still applied, and then the voltage application is stopped and the crystal is cooled to room temperature. After the poling process, the outer circumference of the LT single crystal is ground to adjust the outer diameter of the crystal, and then mechanical processing such as slicing, lapping, and polishing is performed to turn it into an LT substrate. The finally obtained LT substrate is almost colorless and transparent, and its volume resistivity is approximately 10 14 ~10 15 It is about Ω·cm.

[0006] However, in the LT substrate obtained by such a conventional method, due to the pyroelectricity, which is a characteristic of the LT single crystal, electric charge builds up on the substrate surface due to temperature changes during the process of manufacturing surface acoustic wave elements (SAW filters). This causes discharges that destroy the comb electrodes formed on the substrate surface and even causes cracks in the substrate, resulting in a decrease in yield in the element manufacturing process.

[0007] Therefore, in order to eliminate the problems caused by the pyroelectricity of the LT single crystal, a technique for increasing the electrical conductivity has been proposed. For example, Patent Document 1 proposes a method of heat-treating a single crystal wafer obtained by slicing an LT single crystal under a reducing gas atmosphere selected from argon, water, hydrogen, nitrogen, carbon dioxide, carbon monoxide, oxygen, and combinations thereof, and Patent Document 2 proposes a method of embedding the single crystal wafer in a mixture of aluminum powder (Al powder) and aluminum oxide powder (Al2O3 powder) and heat-treating (reducing). The single crystal wafer with increased electrical conductivity (i.e., the LT substrate) absorbs light due to the introduction of oxygen vacancies. The observed color tone of the LT substrate appears reddish brown in transmitted light and black in reflected light, so the reducing treatment that increases electrical conductivity is also called blackening treatment, and such a change in color tone is called blackening. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Japanese Patent Application Publication No. 11-92147 [Patent Document 2] Patent No. 4063191 Summary of the Invention [Problem to be solved by the invention]

[0009] However, unlike lithium niobate single crystals, which have a relatively low melting point of about 1250°C, when the method of Patent Document 1 is applied to LT single crystals, which have a high melting point of about 1650°C, the conductivity of the LT substrate does not increase sufficiently, and there is a problem that the effect of improving defects caused by pyroelectricity is not sufficient. Furthermore, in recent years, there has been a demand to further reduce the volume resistivity, which is a property of LT single crystals, in order to improve the yield in the manufacturing process of surface acoustic wave elements (SAW filters). For example, 9 There is a demand for a value of less than (Ω·cm).

[0010] In the method of Patent Document 2, in which a single crystal wafer obtained by slicing an LT single crystal is embedded in a mixture of aluminum powder (Al powder) and aluminum oxide powder (Al2O3 powder) and then heat-treated, the volume resistivity of the wafer is increased by setting the ratio of Al powder in the mixture to a high value (for example, about 30% by weight). 9 LT substrates with a hardness of about (Ω·cm) have been obtained.

[0011] However, as the ratio of Al powder in the mixed powder increases, color unevenness (differences in shade) caused by localized uneven reduction tends to occur on the substrate surface, and the occurrence rate increases with the increase in the Al powder ratio, resulting in a problem of reduced productivity.

[0012] The present invention has been made in view of these problems, and an object of the present invention is to provide a method for manufacturing a lithium tantalate substrate in which the occurrence of color unevenness (difference in shading) due to localized uneven reduction is suppressed even when the ratio of Al powder in the mixed powder is set high. [Means for solving the problem]

[0013] In order to solve the above problems, the present inventors attempted to improve the method disclosed in Patent Document 2.

[0014] Hereinafter, the manufacturing process of the LT substrate according to Patent Document 2, in which single crystal wafers obtained by slicing LT single crystals are embedded in a mixed powder of Al powder and Al2O3 powder and then heat-treated, will be described. First, as shown in FIG. 1, the mixed powder 2 and single crystal wafers 3 are alternately stacked and filled into a container 1 made of SUS or the like, and the outside of the container 1 with the single crystal wafers 3 embedded in the mixed powder 2 is covered with aluminum foil 4 or the like to seal the open part of the container 1, thereby obtaining a single crystal wafer container 10 in which the single crystal wafers 3 are contained.

[0015] Next, the single crystal wafer containers 10 are stacked in multiple stages to form an assembly 20 as shown in FIG. 2, and a plurality of assemblies 20 are arranged with gaps between each other in the sealed chamber 30 of a heating furnace having the sealed chamber 30. The sealed chamber 30 is then filled with an inert gas such as argon, and each single crystal wafer 3 is heat-treated at a temperature below the Curie temperature of the LT single crystal in the sealed inert gas atmosphere to obtain an LT substrate.

[0016] In order to efficiently manufacture LT substrates, in the method according to Patent Document 2, as many assemblies 20 as possible are placed in a sealed chamber 30 and the single crystal wafers 3 are subjected to heat treatment.

[0017] However, if the number of assemblies 20 arranged in the sealed chamber 30 is increased without consideration, the gaps between the assemblies 20 will decrease, causing variation in the heat treatment atmosphere of each of the assemblies 20, resulting in local temperature unevenness for each of the single crystal wafer housing bodies 10 stacked in multiple stages. It has been confirmed that the reduction conditions for the single crystal wafers 3 housed in each single crystal wafer housing body 10 will also vary due to the local temperature unevenness for each single crystal wafer housing body 10, causing localized reduction unevenness and resulting in color unevenness (differences in shading). It has also been confirmed that the occurrence of color unevenness (differences in shading) is particularly noticeable when the ratio of Al powder in the mixed powder is set high.

[0018] Therefore, in order to find conditions under which local temperature unevenness is unlikely to occur for each single crystal wafer housing body 10, an investigation was carried out while gradually decreasing the number of assemblies 20 arranged in the sealed chamber 30, and it was found that when the spatial occupation rate of all single crystal wafer housing bodies 10 in the sealed chamber 30 is set to 50% or less, local temperature unevenness is unlikely to occur for each single crystal wafer housing body 10, and the occurrence of the above-mentioned color unevenness (difference in shading) is suppressed even if the ratio of Al powder in the mixed powder is set high. The present invention was completed through such technical analysis and discovery.

[0019] That is, the first invention according to the present invention is: A method for producing a lithium tantalate substrate by subjecting a single crystal wafer obtained by slicing a lithium tantalate single crystal to a reduction treatment, comprising the steps of: a step of embedding a plurality of single crystal wafers in a mixture of aluminum powder and aluminum oxide powder filled in a container, and sealing an open portion of the container to form a single crystal wafer container in which the single crystal wafers are housed; In a heating furnace having a sealed chamber, 、 A plurality of single crystal wafer containers The single crystal wafer containers are arranged horizontally so that the gaps between them are uniform. and filling the sealed chamber with an inert gas, and then heat-treating the single crystal wafer at a temperature lower than the Curie temperature of the lithium tantalate single crystal in a sealed atmosphere of the inert gas; The space occupancy rate of all the single crystal wafer containers in the sealed chamber is set to 50% or less.

[0020] Next, the second invention according to the present invention is In the method for producing a lithium tantalate substrate according to the first aspect of the present invention, The container is covered with aluminum foil or titanium foil on the outside to seal the open part of the container. The third invention is In the method for producing a lithium tantalate substrate according to the first or second invention, The container is provided with a plurality of single crystal wafers, the exterior of which is covered with aluminum foil or titanium foil. 、 The sealed chamber is placed on the mounting portion. Even The present invention is characterized in that the electrodes are arranged side by side with gaps between them, The fourth invention is In the method for producing a lithium tantalate substrate according to the third aspect of the present invention, The single crystal wafer containers arranged in a row in the horizontal direction on the placement section of the sealed chamber constitute an assembly in which the single crystal wafer containers are stacked vertically in multiple stages, The fifth invention is, In the method for producing a lithium tantalate substrate according to any one of the first to fourth aspects of the present invention, The mixed powder is characterized in that the ratio of aluminum powder in the mixed powder is 15% by weight to 30% by weight. Effect of the Invention

[0021] According to the method for producing a lithium tantalate substrate of the present invention, Since the spatial occupancy rate of all the single crystal wafer containers in a sealed chamber of a heating furnace is set to 50% or less, it is possible to ensure sufficient gaps between the single crystal wafer containers or between assemblies of the single crystal wafer containers stacked in multiple stages. are arranged horizontally so that they are evenly spaced from each other. This makes it difficult for localized temperature unevenness to occur in each single crystal wafer container, and makes it possible to suppress the occurrence of color unevenness (differences in shade) caused by localized uneven reduction even when the ratio of Al powder in the mixed powder is set high. [Brief description of the drawings]

[0022] [Figure 1] FIG. 2 is an explanatory diagram showing the configuration of a single crystal wafer container in which a single crystal wafer is contained. [Diagram 2] FIG. 13 is an explanatory diagram showing a state in which a plurality of assemblies in which single crystal wafer containers are stacked in multiple stages are placed on a placement portion of a sealed chamber of a heating furnace having the sealed chamber. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] Hereinafter, an embodiment of the present invention will be described in detail.

[0024] The electrical conductivity and color of lithium tantalate (LT) single crystals change depending on the concentration of oxygen vacancies present in the crystal. When oxygen vacancies are introduced into LT single crystals, the valence of some Ta ions changes from 5+ to 4+ due to the need to balance the charge, resulting in electrical conductivity and light absorption. Electrical conductivity occurs when electrons, the carriers, are transported to Ta 5+ Ions and Ta 4+ It is believed that this occurs due to the movement of electrons between ions, and the electrical conductivity of a crystal is determined by the product of the number of carriers per unit volume and the mobility of the carriers. If the mobility is the same, the electrical conductivity is proportional to the number of oxygen vacancies. Also, the color change due to light absorption is thought to be due to the electron level introduced by the oxygen vacancies.

[0025] The method according to Patent Document 2, which the present inventors have attempted to improve, involves embedding a single crystal wafer obtained by slicing an LT single crystal in a mixed powder of Al powder and Al2O3 powder, and heat treating the wafer at a temperature below the Curie temperature of the LT single crystal to manufacture an LT substrate. That is, in the method according to Patent Document 2, embedding the single crystal wafer in the mixed powder makes it possible to reduce the oxygen partial pressure of the inert gas present around the single crystal wafer by the oxidation reaction of Al, and provides sufficient conditions for introducing the oxygen vacancies into the LT single crystal.

[0026] In the method according to Patent Document 2, in order to increase the manufacturing efficiency of the LT substrate, as many assemblies (assemblies of single crystal wafer containers stacked in multiple stages) as possible are placed in the sealed chamber of a heating furnace having the sealed chamber as described above, and the single crystal wafers are heat-treated. However, if the number of assemblies placed in the sealed chamber is increased without reason, the gaps between the assemblies are reduced, causing variations in the heat treatment atmosphere of each assembly, which causes local temperature variations in each single crystal wafer container stacked in multiple stages. Then, the reduction conditions of the single crystal wafers contained in each single crystal wafer container also vary due to the local temperature variations in each single crystal wafer container, causing local reduction variations and causing color variations (shade differences) on the surface of the single crystal wafer. In particular, the occurrence of color variations (shade differences) becomes noticeable when the ratio of Al powder in the mixed powder is set high.

[0027] Therefore, in the present invention, the spatial occupancy rate of all the single crystal wafer containers in the sealed chamber is set to 50% or less, and gaps are secured between the single crystal wafer containers or between assemblies of the single crystal wafer containers stacked in multiple stages. Since sufficient gaps are secured between the single crystal wafer containers or between the assemblies, local temperature unevenness for each single crystal wafer container can be prevented, and local reduction unevenness of the single crystal wafers contained in each single crystal wafer container can be avoided, making it possible to suppress the occurrence of color unevenness (differences in shading).

[0028] 2 shows a configuration in which the assembly 20 in which the single crystal wafer containers 10 shown in FIG. 1 are stacked in multiple stages is arranged on the mounting portion 31 of the sealed chamber 30; however, if the height dimension within the sealed chamber 30 is too small to arrange them as an assembly, or if the height dimension of the single crystal wafer containers 10 is too large to arrange them as an assembly, then the single single crystal wafer containers 10 are arranged side by side in the horizontal direction on the mounting portion 31 of the sealed chamber 30 without forming an assembly.

[0029] Furthermore, when a single single crystal wafer container 10 or an assembly 20 in which single crystal wafer containers 10 are stacked in multiple tiers is placed on the mounting portion 31 of the sealed chamber 30, it is advisable to arrange the single crystal wafer containers 10 or the assembly 20 so that the gaps between them are uniform.

[0030] 1, the container 1 in which the single crystal wafers 3 are embedded in the mixed powder 2 is covered with aluminum foil 4 or the like, but instead of covering with aluminum foil 4 or the like, a structure in which the open part of the container 1 is sealed with a lid or the like may be adopted. Also, in the assembly 20 shown in FIG. 2, the single crystal wafer containers 10 are stacked in multiple stages, but the assembly 20 may be contained in a large container.

[0031] The type of inert gas that fills the sealed chamber 30 includes argon gas, nitrogen gas, and the like. EXAMPLES

[0032] EXAMPLES The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples in any way.

[0033] [Growth of LT single crystals] Using raw material with a congruent composition, a LT single crystal with a diameter of 4 inches was grown by the Czochralski method. The growth atmosphere was a nitrogen-oxygen mixed gas with an oxygen concentration of about 3%. The obtained LT single crystal ingot was transparent and pale yellow in color. Note that, as for the growth method of the LT single crystal, instead of the Czochralski method, for example, the pulling down method may be used.

[0034] Next, the LT single crystal ingot was subjected to a heat treatment to remove thermal strain and a poling treatment to obtain a single polarization, after which the outer periphery was ground, sliced, and polished to obtain a 42° RY (Rotated Y axis) single crystal wafer.

[0035] The resulting 42°RY single crystal wafer was colorless and transparent, with a volume resistivity of 1×10 15 The electrical conductivity was Ω·cm and the Curie temperature was 603°C.

[0036] [Example 1] A SUS cylindrical container with an inner diameter of 112 mmφ, an outer diameter of 120 mmφ, and an outer height of 100 mm was filled with a mixed powder (3 mm thick) of 30% by weight aluminum powder (Al powder) and 70% by weight aluminum oxide powder (Al2O3 powder) and single crystal wafers with a diameter of 100 mmφ and a thickness of 280 μm, which were alternately stacked, and 25 single crystal wafers were embedded at intervals of 3 mm in the mixed powder. The outside of the SUS cylindrical container was then covered with aluminum foil to obtain a single crystal wafer container. Multiple single crystal wafer containers were also manufactured in the same manner.

[0037] Next, a plurality of assemblies each formed by stacking the single crystal wafer containers in three tiers were placed in a sealed chamber of a heating furnace with the chamber so that the gaps between each assemblies were uniform, and then the sealed chamber was filled with argon gas.

[0038] The space occupancy rate of all single crystal wafers in the sealed chamber was 50%.

[0039] The inside of the sealed chamber was then heated in the above-mentioned heating furnace, and the single crystal wafers contained in each single crystal wafer container were heat-treated (blackened) at 580°C for 24 hours. After that, the volume resistivity and the incidence rate of color unevenness (difference in shading) of each single crystal wafer (LT substrate) were examined.

[0040] The volume resistivity was measured by a three-terminal method in accordance with JIS K-6911, and color unevenness (difference in shading) was visually examined.

[0041] The results are shown in Table 1 below.

[0042] [Example 2] The single crystal wafers contained in each single crystal wafer container were heat-treated (blackened) under the same conditions as in Example 1, except that the spatial occupancy rate of all single crystal wafers in the sealed chamber was 40%, and the volume resistivity and color unevenness (shade difference) occurrence rate of each single crystal wafer (LT substrate) after the treatment were examined. These results are also shown in Table 1 below.

[0043] [Comparative Example 1] The single crystal wafers contained in each single crystal wafer container were heat-treated (blackening treatment) under the same conditions as in Example 1, except that the spatial occupancy rate of all single crystal wafers in the sealed chamber was 60%, and the volume resistivity and color unevenness (shade difference) occurrence rate of each single crystal wafer (LT substrate) after treatment were examined. These results are also shown in Table 1 below.

[0044] [Comparative Example 2] The single crystal wafers contained in each single crystal wafer container were heat-treated (blackening treatment) under the same conditions as in Example 1, except that the spatial occupancy rate of all single crystal wafers in the sealed chamber was 70%, and the volume resistivity and color unevenness (shade difference) occurrence rate of each single crystal wafer (LT substrate) after treatment were examined. These results are also shown in Table 1 below.

[0045] [Comparative Example 3] The single crystal wafers contained in each single crystal wafer container were heat-treated (blackening treatment) under the same conditions as in Example 1, except that the spatial occupancy rate of all single crystal wafers in the sealed chamber was 80%, and the volume resistivity and color unevenness (shade difference) occurrence rate of each single crystal wafer (LT substrate) after treatment were examined. These results are also shown in Table 1 below.

[0046] [Comparative Example 4] The single crystal wafers contained in each single crystal wafer container were heat-treated (blackened) under the same conditions as in Example 1, except that the spatial occupancy rate of all single crystal wafers in the sealed chamber was 96%, and the volume resistivity and color unevenness (shade difference) occurrence rate of each single crystal wafer (LT substrate) after the treatment were examined. These results are also shown in Table 1 below.

[0047] [Table 1]

[0048] [Results] (1) In Examples 1 and 2, in which the spatial occupancy rate of all single crystal wafer containers in the sealed chamber is set to 50% or less, it is confirmed that the occurrence rate of color unevenness (difference in shading) is suppressed to 1% or less.

[0049] (2) On the other hand, in Comparative Examples 1 to 4, in which the spatial occupancy rate of all single crystal wafer containers in the sealed chamber exceeds 50%, the occurrence rate of color unevenness (shade difference) is high at 3% to 20%, and it is confirmed that color unevenness (shade difference) is not suppressed. [Industrial Applicability]

[0050] According to the present invention, the occurrence of color unevenness (difference in shading) due to localized uneven reduction can be suppressed, and a lithium tantalate substrate with excellent electrical properties can be manufactured, and therefore the present invention has industrial applicability for use as a substrate material for surface acoustic wave elements (SAW filters). [Explanation of symbols]

[0051] 1 container 2 Mixed powder 3. Single crystal wafer 4. Aluminum foil 10 Single crystal wafer container 20 A collection of single crystal wafer containers stacked in multiple tiers 30 Closed room 31 Placement section

Claims

1. A method for producing a lithium tantalate substrate by subjecting a single crystal wafer obtained by slicing a lithium tantalate single crystal to a reduction treatment, comprising the steps of: a step of embedding a plurality of single crystal wafers in a mixture of aluminum powder and aluminum oxide powder filled in a container, and sealing an open portion of the container to form a single crystal wafer container in which the single crystal wafers are housed; The method includes a step of arranging a plurality of single crystal wafer containers in a sealed chamber of a heating furnace so that the gaps between the single crystal wafer containers are uniform, filling the sealed chamber with an inert gas, and then heat-treating the single crystal wafers in the sealed atmosphere of the inert gas at a temperature lower than the Curie temperature of the lithium tantalate single crystal. A method for manufacturing a lithium tantalate substrate, characterized in that the spatial occupancy rate of all single crystal wafer containers in the sealed chamber is set to 50% or less.

2. 2. The method for producing a lithium tantalate substrate according to claim 1, wherein the outside of the container is covered with aluminum foil or titanium foil to seal an open portion of the container.

3. 3. The method for manufacturing a lithium tantalate substrate according to claim 1, wherein a plurality of single crystal wafer containers, the exterior of which is covered with aluminum foil or titanium foil, are arranged in a horizontal line on the loading portion of the sealed chamber with equal gaps between each other.

4. 4. The method for manufacturing a lithium tantalate substrate according to claim 3, wherein each of the single crystal wafer holders arranged in a row in the horizontal direction on the mounting portion of the sealed chamber constitutes an assembly of single crystal wafer holders stacked vertically in multiple stages.

5. 5. The method for producing a lithium tantalate substrate according to claim 1, wherein the ratio of the aluminum powder in the mixed powder is 15% by weight to 30% by weight.

Citation Information

Patent Citations

  • Lithium tantalate wafer blackening device and using method thereof

    CN110760934A

  • Lithium niobate crystal or lithium tantalate crystal having enhanced performance to decrease charge on crystal surface and method to preliminarily control that kind of crystal

    JP1999092147A

  • Use of concentrated chemicals for preconditioning lithium niobate and lithium tantalate crystals.

    JP2008500731A

  • Method for manufacturing lithium tantalate substrate

    JP2019156655A

  • Production method of lithium tantalate substrate

    JP2019202919A